Inflammatory burden in dialysis patients: the role of alpha defensin - Shapira, Maanit; Abo Aqil, Adib; Zahalka, Ameena; Abumouch, Isis; Amsalem, Naama; Abu Fanne, Rami (Frontiers in Immunology, 2026)
IntroductionThe major neutrophilic peptide alpha-defensin plays a pivotal role in atherogenesis. Atherosclerosis is more frequent in dialysis patients, increasingly ascribed to chronic low-grade inflammation. We investigated the potential association between dialysis treatment and circulating alpha-defensin levels.MethodsIn a cohort of hemodialysis (HD) patients, plasma alpha-defensin concentrations were determined immediately before and after a dialysis session. Blood samples were also tested for CBC, CRP, lipid profile, and troponin levels. Body weight change, Urea Reduction Ratio and Kt/V were used to assess dialysis adequacy. Patients were divided into two groups based on alpha-defensin increase post dialysis. Groups were compared for dialysis adequacy, CBC, CRP, LDL levels, and the incidence of new documented coronary artery narrowing post HD initiation. The study was approved by the local IRB and all patients were consented.ResultsA total of 37 HD patients (55% males, median age 66.5 (60.3–78 years)) were recruited. There was a marked surge in median alpha-defensin levels after HD [11,571 vs. 16,661 ng/ml, p=0.009]. Overall, alpha-defensin levels increased in 65% of cases, whereas CRP levels showed no significant rise following dialysis. Similarly, platelet and neutrophil counts exhibited no significant change. Kt/V values were found favorable in HD patients with alpha-defensin decrease (1.48 vs. 1.37, P = 0.24), corresponding to a higher body weight decrease post dialysis (2.4% vs. 1.75%). Moreover, the HD group with alpha-defensin increase was more prone to sustain new cardiovascular events (12.5% vs. 0% at a median time of 5 (3.75-6.57) years), despite demonstrating a better blood lipid profile (LDL 63 vs. 87 mg/dl).ConclusionHD is an alpha-defensin generating procedure. Patients are potentially predisposed to atherosclerosis because of their enhanced alpha defensin secretion. alpha-defensin might evolve as a potential therapeutic target for atherosclerosis mitigation in this high-risk population. However, this remains to be validated in future research.